Epistemologi Filsafat dan Sains dalam Dunia Akademik Menurut Teori Falsifikasi Karl Raimund Popper (Pusat Riset dan Inovasi Nasional, 2026)
A problem that is often debated by both the western and eastern world is the problem of determining the truth of a scientific field or theory. In western science, a thought emerged from a philosopher, namely the theory of falsification put forward by Karl Raymond Popper. In his theory Popper argues that the truth of a science is not determined through justification (verification), but through refuting the propositions that science itself builds (falsification). The study of Popper's falsification has been very widely published and discussed in various writings, especially in Islamic studies and science (science). In this article, the author tries to briefly describe the urgency of Karl R. Popper's thought in the academic field. The method used in writing this article is library research (literature review), using relevant documents, journals, and research. Through this research, it is known that the application of Karl Raimund Popeer's theory of falsification is very important in the academic field. This is evidenced by the concept of falsification which is used to determine the scientific knowledge. In addition, the concept of falsification was used long before Popper introduced the theory. One of them is used by the Muslim philosopher Imam Al-Gazali in defending and proving his arguments and thoughts. In the development of scientific methods, the principle of falsification plays an important role in strengthening scientific theory because it serves as evidence to disqualify other irrelevant theories.